A randomized controlled trial to evaluate the effectiveness of a novel mouth rinse in patients with gingivitis - Bianca A. Newman; Claire N. Rosebrough; Ryan A. Tamashiro; Ana P. Dias Ribeiro; Joan A. Whitlock; Gurjit Sidhu; Ikramuddin Aukhil; Dianne Y. Porral; Ann Progulske-Fox; Matthew F. Myntti; Gary P. Wang (BMC, 2022)
Abstract Background This single-center, randomized controlled trial aimed to determine the effectiveness of a novel, biofilm-disrupting, mouth rinse that combines Cetylpyridinium chloride (CPC) and essential oils in preventing re-accumulation of supragingival plaque and supragingival microbiome in patients with gingivitis after dental prophylaxis. Methods One hundred eighteen participants were randomly assigned in a 1:1 ratio to receive twice-daily test mouth rinse (59) or carrier rinse control (59) for 12 weeks after dental prophylaxis. Results In a per-protocol analysis that included patients who completed the intervention, the treatment group (39) had significantly lower supragingival plaque scores at 6 and 12 weeks compared to the control group (41; p = 0.022). Both groups showed similar improvement in gingivitis score, but neither group had improvement in bleeding score or probing depth. Thirty-eight (29%) patients did not complete the study due to loss of follow-up (17) or early discontinuation of the assigned intervention (21). Microbiome sequencing showed that the treatment rinse significantly depleted abundant and prevalent members of the supragingival plaque microbiome consortium. Conclusions Among patients with gingivitis, the novel mouth rinse significantly reduced re-accumulation of supragingival plaque following dental prophylaxis by depleting supragingival plaque microbiome. However, long-term adherence to the rinse may be limited by adverse effects ( ClinicalTrials.gov number, NCT03154021).